A swarm of bees in May - Kinman, Charles Franklin (My University, 1904)
Introduction: In its characteristics the Italian bee as we find it today is not different from that found over two thousand years ago, by Spinola, in a part of Italy called Liguria. No doubt bees of this variety existed in that country long before they were reported, for at that time they had assumed a disposition and habits that could be established only by unchanging surroundings, such as a particular food, protection against enemies, and isolation from other varieties of bees which would cause their characteristics to vary. The variety was well established through the isolation, as the seas and the snow covered mountains which completly surround Italy made it impossible for other insects to enter this territory. There are many varieties of apidae. However we will not consider any except the Ligurian or Italian bee, as it is known, since it is far more numerous and important economically than any other variety of bees and the complete exclusion of other varieties by them is only a matter of time. While there is nothing but what is interesting and instructing about the work of the Italian bee, we will confine ourself as near as possible to their work of a single month, May.
Citation: Kinman, Charles Franklin. A swarm of bees in May. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Bees; Italian Bees; Animal Lifestyles; May; Spring; Theses